Assessment of sexual functions in partners of women with complaints of urinary incontinence - Muzaffer Oguz Keles; Selahattin Caliskan; Ali Murat Gokce; Mustafa Gunes (International Brazilian Journal of Urology)
ABSTRACT Aim: Investigation of the erectile functions in partners of women with urinary incontinence problems. Materials and Methods: Sexually active female patients over the age of 18 years with complaints of urinary incontinence (n=30) (Group-1), and without urinary incontinence (n=30) (Group-2, controls) were included this study. Evaluation of the patients were done at Erzincan Mengücek Gazi Training and Research Hospital's urology outpatient clinic between June 2012 and January 2013. Partners of group-1 and group-2 were asked to fill in the 5-item International Index of Erectile Function (IIEF-5) questionnaire, and then the scores of the two groups were compared for statistically significant differences. Results: Among the partners of the group-1 patients, 15 (50%) had mild erectile dysfunction (ED), 11 (36.6%) had moderate ED, 1 (3.4%) had severe ED, and erectile function was normal in the remaining 3 (10%). Among the partners of group-2 patients, 15 (50%) had mild ED, 7 had moderate ED, 1 (3.4%) had severe ED, and 7 (23.3%) had normal erectile function. Compared to the spouses of group-2 patients, ED was more prevalent among the spouses of group-1 patients. Conclusion: Erectile function in the partners of women with urinary incontinence may be adversely affected by the UI of their partners.